Impatiens fujianensis (Balsaminaceae), a new species from China: evidence from morphological and molecular analyses - Ma, Liang; Chen, Xin–Yan; Zhou, Cheng-Yuan; Chen, Shi-Pin (Phytotaxa, 2024)
We here describe and illustrate a new species, Impatiens fujianensis (Balsaminaceae), from Fujian Province in southern China. Morphological comparisons indicated that I. fujianensis is similar to I. noli-tangere and I. yilingiana but showed distinct differences in leaves, inflorescences, pedicels and flowers. The molecular phylogenetic analysis based on nuclear ribosomal internal transcribed spacer (ITS) and two plastid regions (atpB-rbcL and trnL-F) indicated that I. fujianensis is a distinct species, which forms an independent lineage. Both morphological and molecular evidence supported the status of I. fujianensis as a new species.